HOW TO USE CALCULATOR CASIO FX-570MS IN NUMERICAL METHODS - Tay Kim Gaik (2006)
This book is written specially for university students who take up the subject of Numerical Methods. It intends to give an idea on how to use the Calculator Casio FX-570MS in Numerical Methods. The CALC memory in Calculator Casio FX-570MS provides 9 variables (A, B, C, D, E, F, X, Y, and M). User can use these variables to input several numerical iteration formulas for calculating with different values. Once the formulas are entered, it can be recalled back easily for the next calculation. These abilities are indeed helpful in doing faster and accurate manual numerical iteration calculating during practice exercises and examination.